Studies on the Evaluation of the Half-sib Progenies to Identify the Prepotency of the Mother Clones of Hevea brasiliensis in Meghalaya - Chandra, U.; Reju, M. J.; Singh, R. P.; Das, G.; Panda, D.; Mydin, K. K. (International Journal of Bio-resource and Stress Management, 2016)
Two field experiments were conducted at Ganolgre Farm in the year 2008 and 2009, respectively under the Rubber Research Institute of India, Regional Research Station, Tura, West Garo Hills, Meghalaya (India) to identify the prepotent mother clones suitable for future breeding programmes in this region. Fully matured seeds were collected directly from the trees of the individual clones of Hevea and put on the germination bed. The germinated seeds were planted in two fields 10 days after collection. Growth observations viz. plant height, plant girth, number of whorls and the number of leaves were recorded annually before the start of the test tapping. After that all the seedlings were subjected to 10 test tapping. In 2008-trial the selected plants showed mean test tap yield range from 3.3–6.06 g t-1 10 t-1 in which the maximum yield was recorded in the clone PB 5/51 (6.06 g t-1 10 t-1) and minimum was in RRIM 600 (3.3 g t-110 t-1) whereas in 2009-trial the selected plants showed mean test tap yield range from 2.4–5.4 g t-1 10 t-1. The maximum yield in 2009 trial was recorded in RRII 105 (5.4 g t-1 10 t-1) and minimum was in GL 1 (2.4 g t-1 10 t-1). On the basis of the test tap yield the top yielding seedlings were selected and the selected bud-woods are maintained in the field for further breeding evaluation programme.